Measuring, defining, and valuing change: A database on development indicators for policy-makers, activists, and researchers - Prinsen, Gerard; Purcell, Gisela (Institute of Development Studies, Massey University, 2013)
The use of indicators in international development has increased exponentially since the 1990s. Composite and proxy indicators are used to measure a wide range of concepts but their shortcomings have been widely critiqued. Through a review of over 300 documents, this paper gives a brief history of the rise of “indicatorology” and then summarizes the key challenges in three categories: technical/operational, political/strategic and epistemological/conceptual. Technical challenges faced by development practitioners revolve around the over-simplification of complex issues and the conflation of the goals with indicators. Political challenges involve the inherent power of indicators and the implications they have for policy making. Epistemological challenges question how to balance scientific rigor with local knowledge in the creation and use of indicators. A database of all publications used in this research is being made accessible to development practitioners and researchers via Massey University – watch this space!
Keywords: Indicators; Databases; Poverty measurement; Monitoring and evaluation; Assessment; Results based management